2016
DOI: 10.1515/acve-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Antioxidant Capacity and Activities of Blood Glutathione Peroxidase and Superoxide Dismutase Determined in Healthy Dogs by Using Commercially Available Kits

Abstract: Data on the values of selected blood antioxidant parameters, i.e. total antioxidant capacity, glutathione peroxidase, and superoxide dismutase in healthy dogs, are lacking. There are no published accepted standard reference methods for their determination. The aim of this study was to determine the values of plasma total antioxidant capacity and the activities of whole blood glutathione peroxidase and erythrocyte superoxide dismutase in 30 healthy client-owned dogs (19 females, 11 males). The effect of age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 56 publications
8
14
0
2
Order By: Relevance
“…40 A recent study in healthy dogs reports a tendency of higher GPX activity in geriatric dogs. 43 MDA concentrations did not differ significantly between controls and individual ISACHC groups; however, significantly lower MDA concentrations were found in the ISA-CHC II group compared to the ISACHC I and ISACHC III groups. The latter might be the result of stochastic chance § Significantly lower in comparison with ISACHC I (p = 0.004) and ISACHC III (p = 0.017).…”
Section: Discussionmentioning
confidence: 60%
“…40 A recent study in healthy dogs reports a tendency of higher GPX activity in geriatric dogs. 43 MDA concentrations did not differ significantly between controls and individual ISACHC groups; however, significantly lower MDA concentrations were found in the ISA-CHC II group compared to the ISACHC I and ISACHC III groups. The latter might be the result of stochastic chance § Significantly lower in comparison with ISACHC I (p = 0.004) and ISACHC III (p = 0.017).…”
Section: Discussionmentioning
confidence: 60%
“…Oxidative stress encompasses not only the rate of RS production, but also the antioxidant system and the oxidative damage accumulated when the antioxidant system cannot keep up with RS production [ 54 ]. There is evidence that antioxidant enzymes are under endocrine control and can be affected by sex and age of the dog [ 55 ]. Thus, as predicted, we found a significant age class difference in GSH, where older dogs, despite their size class, showed an increase in GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Though, we do not see a significant reduction in GSH in large breed dogs, there may be other antioxidant enzymes that are being reduced in function and, thus, allowing for an accumulation of oxidative damage in larger breed dogs. Others have shown an age-related increase in SOD activity, another antioxidant enzyme measured in blood [ 55 ]. Surprisingly, we found no differences in average RS production across size and age classes in primary fibroblasts of dogs, though it is common to assume that with age, RS production should increase [ 60 ], many studies have not shown a strong correlation between RS production and lifespan [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uzyskane wyniki krwinkowej aktywności SOD są podobne do wyników stwierdzanych u ludzi (8,9) i psów (2,19). Wykazana zależność istotnie niższej aktywności SOD u psów z zaćmą jest zbieżna z wy-nikami uzyskiwanymi u ludzi z ARC, o czym donoszą liczni autorzy (3,9,13,25).…”
Section: Wyniki I Omówienieunclassified
“…Uzyskane wyniki krwinkowej aktywności GPX u psów są podobne do uzyskanych u ludzi (3, 4, 9) i psów (2,19). Obserwowana w badaniach własnych tendencja do obniżania aktywności GPX w przebiegu zaćmy koresponduje ze studiami wykonanymi u ludzi, u których stwierdzono istotnie niższą aktywność u osób z ARC (4,8,9).…”
Section: Wyniki I Omówienieunclassified